2016
DOI: 10.1007/s10750-016-2679-9
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profiles are biomarkers of fish habitat use in a river-floodplain ecosystem

Abstract: 7Fatty acid (FA) analyses of fish tissues offer the potential to gain new knowledge of habitat-or 8 forage-specific energy inputs to fishes in river-floodplain ecosystems, although limited 9 information exists regarding among-habitat differences in FA biomarkers. The goal of this study 10 was to determine if differences in fish FA profiles among main channel and connected and 11 disconnected floodplain lakes exist in large river-floodplain systems. Bluegill Lepomis 12 macrochirus FA profiles were generated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…DHA is selectively and highly retained over other PUFA in fish, consistent with all reviewed datasets. It is still not clear if the high retention of DHA in fish is mainly driven by dietary DHA (Dayhuff, ; Rude et al., ; Young et al., ) or by endogenous PUFA conversion (Henrotte et al., ; Hixson et al., ; Murray et al., ; Oboh, Betancor, Tocher, & Monroig, ; Tocher & Dick, ). Our results showed that DHA retention in fishes from subtropical rivers is greater than that from temperate rivers, suggesting fishes may spend extra energy to synthesise LC‐PUFA under high temperature leading to more energy loss (Farkas, Csengeri, Majoros, & Oláh, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…DHA is selectively and highly retained over other PUFA in fish, consistent with all reviewed datasets. It is still not clear if the high retention of DHA in fish is mainly driven by dietary DHA (Dayhuff, ; Rude et al., ; Young et al., ) or by endogenous PUFA conversion (Henrotte et al., ; Hixson et al., ; Murray et al., ; Oboh, Betancor, Tocher, & Monroig, ; Tocher & Dick, ). Our results showed that DHA retention in fishes from subtropical rivers is greater than that from temperate rivers, suggesting fishes may spend extra energy to synthesise LC‐PUFA under high temperature leading to more energy loss (Farkas, Csengeri, Majoros, & Oláh, ).…”
Section: Discussionmentioning
confidence: 99%
“…Algal PUFA variations induced by river longitudinal gradients significantly affected fish PUFA composition (Dayhuff, ; Rude et al., ; Young et al., ). Interacted with light availability, nutrient inputs and temperature, river longitudinal gradients also determine fish distribution (Buisson, Blanc, & Grenouillet, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spatial variation in lower food web processes can also exert strong influences on spatial heterogeneity in food web structure in aquatic systems (Crowder & Cooper, 1982;Rude, Trushenski, & Whitledge, 2016;Sass, Gille, Hinke, & Kitchell, 2006). The southwest portion of the lake receives relatively little allochthonous nutrient input from different land use types (forested vs. urban and agriculture) compared to other sites, which may affect fatty acid availability by changing primary production pathways from bacterial and detrital sources to phytoplankton production (Larson et al, 2013;Lau et al, 2012;Rude et al, 2016;Scharold, Corry, Yurista, & Kelly, 2015). Similar west-to-east spatial patterns have been observed in the microbial communities, nitrogen cycling dynamics and nearshore primary productivity in Lake Michigan (Gardner et al, 2004;Hutton Stadig, 2016;Turschak et al, 2018).…”
Section: Spatial Variation In Trophic Diversity and Niche Sizementioning
confidence: 99%